PENGARUH PELAYANAN TERHADAP KEPUASAN MAHASISWA MENGGUNAKAN RUANG BACA KAMPUS 1 FKIP UNTAN PONTIANAK - Sembiring, Ineke Yemima; Bahari, Yohanes; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is aimed to find out the effect of service on student satisfaction in utilizing Reading Room Kampus 1 FKIP Untan Pontianak. The method used in this study is descriptive quantitative research. In this study, the sample were studens who lend from Reading Room Kampus 1 FKIP Untan Pontianak and the data were collected using a questionnaire about service with 3 indicators namely Intangibility, Unstorability, and Customization. The results showed that from the 3 indicators, the average of each of them included in the goog category, and student satisfaction with 3 indicators being divoted, loyal and royal, and giving favorable comments about the company or its products and service. Based on data analysis techniques, the significant effect of t count > t table (3,465>1,97435) than Ho was rejected and Ha was accepted. As the significant degree is 5%, therefore Ho is rejected and Ha is accepted. The magnitude of the service effect on students satisfaction is 0,062 signifies that the percentage is 62% and the rest is affected by other variables that are not avaliable in this study.Keywords: Service, Students’ Satisfaction, Reading Room